Enriching Floral Basket... Sunken nursery bed for raising early flower seedlings - Thakur, Priyanka; Joshi, Ajay; Chauhan, Vimal; Chauhan, Neena (Indian Horticulture, 2019)
The sunken nursery bed technique is successful in early germination of seeds at enhanced germination rate. This is a cheaper technique which saves time and helps in early and ensured supply of summer season flower nursery to end users.